Angiotensinergic and GABAergic transmission in the medial preoptic area: role in urinary bladder and cardiovascular control in female rats - Daiuto, Sergio A.; de Carvalho, Rodrigo P.; Vale, Bárbara do; Dsouki, Nuha A.; Giannocco, Gisele; Cafarchio, Eduardo M.; Aronsson, Patrik; Sato, Monica A. (Frontiers in Physiology, 2023)
The medial preoptic area(mPOA)participates in thermoregulatory control and blood pressure modulation as shown by studies with electrical stimulation of this area or cobalt chloride injection,a non-selective synapse inhibitor.This study aimed to investigate whether angiotensinII(Ang II)and GABA could act or not in the mPOA to mediate the cardiovascular and micturition control pathways. Female Wistar rats were submitted to stereotaxic surgery for implantation of a guide cannula into the mPOA 7 days prior to the experiments.Afterwards, the animals were isoflurane-anesthetized and submitted to the catheterization of the femoral artery and vein and urinary bladder cannulation for mean arterial pressure(MAP),heart rate(HR),and intravesical pressure(IP)recordings, respectively. After the baseline MAP, HR, and IP recordings for 15 min, AngII(0.1 nM, 1 µL),losartan(AT-1 receptor antagonist,100 nM, 1 µL),GABA(50 mM, 1 µL) or saline(1 µL)were injected into the mPOA, and the variables were measured for additional 30 min. In a different group of rats,the AT-1 receptor, angiotensin II converting enzyme(ACE), and GABAa receptor gene expression was evaluated in mPOA samples by qPCR. The data are as mean ± SEM and submitted to One-way ANOVA or paired Student t-test(P<0.05).The injection of Ang II into the mPOA evoked a significant hypotension (-37±10 mmHg,p=0.024) and bradycardia(-47±20 bpm,p=0.030)compared to saline(+1±1 mmHg and +6±2 bpm).A significant increase in IP was observed after Ang II injection into the mPOA(+72.25±17.91%,p=0.015 vs.-1.80±2.98%,saline).No significant changes were observed in MAP, HR and IP after the losartan injection in the mPOA compared to saline injection. Injection of GABA into the mPOA evoked a significant fall in MAP and HR(-68±2mmHg,p<0.0001 and -115±14bpm, p=0.0002 vs. -1±1mmHg and +4±2 bpm, saline),but no significant changes were observed in IP.The AT-1 receptor, ACE and GABA receptor mRNA expression was observed in all mPOA samples. Therefore,Ang II mediated transmission in the mPOA is involved in the cardiovascular regulation and in the control of central micturition pathways. A phasic control dependent on AT-1 receptors in the mPOA seems to be involved in the regulation of those cardiovascular and intravesical parameters. In contrast, GABAergic transmission in the mPOA participates in the pathways of cardiovascular control in anesthetized rats, nevertheless,this neurotransmission is not involved in the micturition control.